The Interstitial Duplication 15q11.2‐q13 Syndrome Includes Autism, Mild Facial Anomalies and a Characteristic EEG Signature. Issue 4 (14th March 2013) - Urraca, Nora; Cleary, Julie; Brewer, Victoria; Pivnick, Eniko K.; McVicar, Kathryn; Thibert, Ronald L.; Schanen, N. Carolyn; Esmer, Carmen; Lamport, Dustin; Reiter, Lawrence T.
<x xml:space="preserve">Abstract</x> Chromosomal copy number variants (CNV) are the most common genetic lesion found in autism. Many autism‐associated CNVs are duplications of chromosome 15q. Although most cases of interstitial (int) dup(15) that present clinically are de novo and maternally derived or inherited, both pathogenic and unaffected paternal duplications of 15q have been identified. We performed a phenotype/genotype analysis of individuals with interstitial 15q duplications to broaden our understanding of the 15q syndrome and investigate the contribution of 15q duplication to increased autism risk. All subjects were recruited solely on the basis of interstitial duplication 15q11.2‐q13 status. Comparative array genome hybridization was used to determine the duplication size and boundaries while the methylation status of the maternally methylated small nuclear ribonucleoprotein polypeptide N gene was used to determine the parent of origin of the duplication. We determined the duplication size and parental origin for 14 int dup(15) subjects: 10 maternal and 4 paternal cases. The majority of int dup(15) cases recruited were maternal in origin, most likely due to our finding that maternal duplication was coincident with autism spectrum disorder. The size of the duplication did not correlate with the severity of the phenotype as established by Autism Diagnostic Observation Scale calibrated severity score. We identified phenotypes not comprehensively described before in this cohort including mild facial dysmorphism, sleep problems and an unusual electroencephalogram variant. Our results are consistent with the hypothesis that the maternally expressed ubiquitin protein ligase E3A gene is primarily responsible for the autism phenotype in int dup(15) since all maternal cases tested presented on the autism spectrum. Autism Res 2013, ●●: ●●–●●. © 2013 International Society for Autism Research, Wiley Periodicals, Inc.